Hubungan Antara Kecenderungan Pola Asuh Otoriter (Authoritarian Parenting Style) dengan Gejala Perilaku Agresif Pada Remaja - Dewi, Ni Putu Ayu Resitha; Susilawati, Luh Kadek Pande Ary (Jurnal Psikologi Udayana, 2016)
Aggressive behavior is an action which aims to hurt or to injure someone else. Aggressive behavior could appear at any age, without exception for the adolescent. The adolescent is described as a storm and stress period, that is the emotional turbulence that accompanied by the decrease of ability to manage their emotion with the result that potentially to form an aggressive behavior. One of the factor that cause aggressive behavior is the authoritarian parenting style. The authoritarian parenting style done by the parents can bring some impacts for the children. The children which always prosecuted to do their parents’ wish will feel frustrated which makes them to act freely and behave aggressively when they are outside home ( Sarwono,1988). This research is purposed to know the significant relationship between tendency of authoritarian parenting style with indication of aggressive behavior in adolescents. The subject of this research is 258 adolescents at the age of 13 and 18 years old. The method used in this research is quantitative methods with correlational approach. The sampling technique used is multistage random sampling . The measuring tool that used is authoritative upbringing scale (31 aitem; rxx` = 0,915) and aggressive behavior scale (39 aitem; rxx` = 0,902). The main data in this research is analyzed by using spearman nonparametric correlation analysis with correlation value 0,314 and probability value 0,000. The supporting data is analyzed by using Independent Sample Test Analysis to see the difference of aggressive behaviour if it is observed from the age and the gender. The result of this research which analyzed by using Independent Sample Test indicate that there is no difference of aggressive behaviour based on the gender and age of research subject. Keywords : Authoritarian Parenting Style., Aggressive Behaviour, Adolescent.